SUBLIMINAL MESSAGES IN PRISON - Nadarevic, Damir (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2022)
There are subliminal messages all around us, whether we want to admit it or not. The possibilities of consciously influencing the unconscious with the aim of manipulating human behaviour have been explored since as far back as 1884 (American researchers Pierce and Jastrow). Prisons are a symbol of the power of the state, an instrument of fear and, ultimately, the places for housing people whose behaviour is unacceptable to the community. Therefore, certain forms of manipulation of prisoners, disguised as re-education and resocialisation, as declarative goals of punishment, are considered a legitimate "right" of the state. What this paper will cover in particular is the detection of subliminal messages as manipulative instruments imprisoned persons are exposed to while serving a prison sentence. The paper gives a definition of subliminal messages, shows the ways in which such can be inserted into certain content of activities performed in prison, and their re-educational value is assessed. Special emphasis is placed on prison symbols as carriers of subliminal messages, on the architecture of the prison itself, the layout of the rooms used by employees and rooms where prisoners spend their time, the colours of those rooms, smells and sounds inside them, different ways of artistic expression but also on the employee-prisoner relations as well as peer relationships among prisoners themselves, their customs, ceremonies, discourse and gestures. All of the above, in the end, has at least two dimensions: a declarative (regulated by law) and, for the purpose of understanding the prison and its tasks, a much more valuable, covert, subliminal one.
Keywords: prison, subliminal, resocialisation, prisoners